Analisis Pendapat Mazhab Syafi’i Terhadap Keabsahan Mahar Berupa Ayat Alquran - Muhammad Rizki Ambiya, Azhar, Diyan Yusri (Mediation : Journal Of Law, 2022)
The dowry must be given by the groom to the bride he marries. If the dowry is not given, the marriage remains valid, but it incurs a sin for the groom for not fulfilling his obligations. Dowry can be in the form of valuable objects or services provided to the bride. However, in practice there are those who make memorizing the Koran a dowry. From these problems, it is necessary to conduct research from the point of view of the Syafi'i School, which is the school that is predominantly adhered to by the people of Indonesia regarding the legitimacy of dowry in the form of verses from the Koran. This study aims to find out the views in the Shafi'i School regarding dowry in the form of Qur'anic verses and its validity as dowry. The type of research used by the authors is qualitative research with a field study and literature study approach. The data were collected using literature study techniques, interviews, and document research. The primary data sources are the results of interviews with Tanjung Pura Sub-District KUA employees and the books of the Syafi'i School of Jurisprudence, and the secondary data sources are relevant books. The data is then collected, reduced, presented and concluded. The results of his research are: first, according to Imam Syafi'i, the purpose of the dowry of Qur'anic verses is to teach them to his wife, namely the science of memorizing and reading the Qur'an properly and correctly; second, Imam Syafi'i argues that the dowry is valid with the verses of the Koran, namely by teaching the verses that have been memorized to the wife he marries, where the teaching can be assessed as a service.